The Effect of Competence and Workload on Employee Performance Mediated by Work Motivation - Yohana Riyantisa; Survival (Optima Science, 2024)
This research aims to empirically test and prove the role of competency and workload on employee performance which is mediated by the work motivation of library employees at the Malang Raya Library and Archives Service. Theoretically, the results of this research are expected to enrich and complete the body of knowledge in the field of strategic management, so that it can be useful for academics and practitioners. This research is explanatory research that tests and explains research variables using a quantitative approach with survey methods and using the Structural Equation Modeling model with Partial Least Squares (SEM-PLS) version 4. The population in this research is library employees at the Malang Library and Archives Service Raya, numbering 50 people. The size or number of samples in this research was determined based on the theory developed by Slovin with a value of e = 5% so that a sample of 50 people was obtained. The results of this research show that employee competence has a direct positive impact on work motivation and employee performance. Work motivation also acts as a link between employee competence and performance. However, workload does not have a direct influence or through work motivation on employee performance. Therefore, it is necessary to focus on developing employee competency and efforts to increase work motivation to optimize employee performance, while managing workload effectively is also important for employee welfare.